Modern Dance Center Di Kota Pekanbaru Dengan Pendekatan Arsitektur Metafora - Anjani Eka Putra Daely; Gun Faisal; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Modern dance is currently very popular in Pekanbaru city because modern dance identical with everything that is new and not difficult to learn, this is proven by many modern dance communities in Pekanbaru city. From year to year the modern dance community in Pekanbaru cityis increasing, along with many large annual events held in Pekanbaru city. The method in this design is to use the metaphor Architecture approach by applying all its characteristics. The conceptthat used is arm wave, obtained from one of the modern dance movements. The application of thisconcept to the design lies in the shape of the building and landscape design.Key word: Dance, Modern Dance, Dance Community, Metaphor Architecture